Implementasi Kebijakan Retribusi Pelayanan Persampahan dan Kebersihan Dalam Meningkatkan Pendapatan Asli Daerah Dikota Gorontalo - Desi Handayani; Sri Yulianti Mozin; Yacob Noho Nani (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2026)
This study aims to analyze the implementation of the waste and sanitation service levy policy in increasing the Regional Original Income (PAD) of Gorontalo City. The research employed a qualitative descriptive approach at the Environmental Agency (DLH) of Gorontalo City. Data were collected through observation, interviews, and documentation involving government officials, collectors, and community members in Hulonthalangi, Kota Selatan, and Sipatana districts. The findings indicate that policy implementation has not been optimal. Although waste collection services and levy collection have been conducted, their contribution to increasing PAD remains limited. The main obstacles include weak communication and uneven policy socialization, limited human resources and supporting facilities, low implementer motivation due to workload and insufficient incentives, and inconsistent implementation of Standard Operating Procedures (SOP) accompanied by weak inter-agency coordination. These findings are consistent with Edward III’s policy implementation theory, which emphasizes communication, resources, disposition, and bureaucratic structure as key determinants of successful implementation. The study concludes that strengthening communication, improving resources, enhancing incentives, and optimizing bureaucratic coordination are essential to increase policy effectiveness and maximize local revenue.